SINKRONISASI PASAR TENAGA KERJA: ANALISIS PERAN SMK PADA PERKEMBANGAN PASAR TENAGA KERJA DI INDONESIA - Goldy Dharmawan; Wisnu Harto Adi Wijoyo (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2022)
This research tries to evaluate the efficiency of the vocational school distribution by examining the supply-demand pattern of vocational school graduates at the national and regional levels in Indonesia using employment, underemployment, and wage level as the indicators. We use the recent data of the Indonesian National Labor Force Survey (Sakernas) and Core Educational Data (Dapodik) to conduct statistical analysis assessing the vocational school graduates. The result indicates that vocational school graduates’ odds to get a job is generally better than the high school graduates. However, the study finds that high school graduates get higher wage level compared to vocational school graduates. Moreover, there is a different pattern of enrolment of the vocational study program in different regions. The results also suggest that job training with a certificate has a better effect on higher earnings than graduating vocational schools. The result can be considered as a valuable input in the form of policy recommendation to recalculate which study program that is needed in which region and providing alternatives to take job-training as a strategy to boost workers wage level.